Pharmacological targeting of actin-dependent dynamin oligomerization ameliorates chronic kidney disease in diverse animal models - Schiffer, Mario; Teng, Beina; Gu, Changkyu; Shchedrina, Valentina A.; Kasaikina, Marina; Pham, Vincent A.; Hanke, Nils; Rong, Song; Gueler, Faikah; Schroder, Patricia; Tossidou, Irini; Park, Joon-Keun; et al. (Nature Medicine, 2015)
Dysregulation of the actin cytoskeleton in podocytes represents a common pathway in the pathogenesis of proteinuria across a spectrum of chronic kidney diseases (CKD). The GTPase dynamin has been implicated in the maintenance of cellular architecture in podocytes through its direct interaction with actin. Furthermore, the propensity of dynamin to oligomerize into higher-order structures in an actin-dependent manner and to cross-link actin microfilaments into higher-order structures has been correlated with increased actin polymerization and global organization of the actin cytoskeleton in the cell. We found that use of the small molecule Bis-T-23, which promotes actin-dependent dynamin oligomerization and thus increased actin polymerization in injured podocytes, was sufficient to improve renal health in diverse models of both transient kidney disease and CKD. In particular, administration of Bis-T-23 in these renal disease models restored the normal ultrastructure of podocyte foot processes, lowered proteinuria, lowered collagen IV deposits in the mesangial matrix, diminished mesangial matrix expansion and extended lifespan. These results further establish that alterations in the actin cytoskeleton of kidney podocytes is a common hallmark of CKD, while also underscoring the substantial regenerative potential of injured glomeruli and identifying the oligomerization cycle of dynamin as an attractive potential therapeutic target to treat CKD.
EVALuna2:34565